Errata: A Simulation Study of Effects of Multicollinearity and Autocorrelation on Estimates of Parameters - Chiu, John S. Y. (Journal of Financial and Quantitative Analysis, 1966)
John S. Y. Chiu, Errata: A Simulation Study of Effects of Multicollinearity and Autocorrelation on Estimates of Parameters, The Journal of Financial and Quantitative Analysis, Vol. 1, No. 4 (Dec., 1966), pp. 126-127